The influence of market orientation and relationship quality on relationship outcome between public universities and their associated colleges in Malaysia / Zainuddin Zakaria - Zakaria, Zainuddin (Institute of Graduate Studies, UiTM, 2012)
This thesis is the culmination of more than three years of effort to study the elements and factors that are able to influence the quality of relationship. The core elements identified in the conceptual model are trust and commitment. Together with three dimensions of relational norms, these variables are hypothesised to influence the economic, non-economic satisfaction and the intention of the partners to continue their relationship in the future. Two antecedents have also been identified in the conceptual model, namely are the organisation’s perception of its own market orientation and their perception of their partners’ market orientation.